Global small‐angle scattering data analysis of inverted hexagonal phases. Issue 2 (28th March 2019) - Frewein, Moritz P. K.; Rumetshofer, Michael; Pabst, Georg
Abstract : A global small‐angle scattering model for unoriented, fully hydrated, inverted hexagonal phases is provided. The model is evaluated using Bayesian probability theory to obtain reliable estimates for the structural parameters. Abstract : A global analysis model has been developed for randomly oriented, fully hydrated, inverted hexagonal (HII ) phases formed by many amphiphiles in aqueous solution, including membrane lipids. The model is based on a structure factor for hexagonally packed rods and a compositional model for the scattering length density, enabling also the analysis of positionally weakly correlated HII phases. Bayesian probability theory was used for optimization of the adjustable parameters, which allows parameter correlations to be retrieved in much more detail than standard analysis techniques and thereby enables a realistic error analysis. The model was applied to different phosphatidylethanolamines, including previously unreported HII data for diC14:0 and diC16:1 phosphatidylethanolamine. The extracted structural features include intrinsic lipid curvature, hydrocarbon chain length and area per lipid at the position of the neutral plane.